A pilot ASKAP survey of radio transient events in the region around the intermittent pulsar PSR J1107-5907 - Hobbs, G.; Heywood, I.; Bell, M.; Kerr, M.; Rowlinson, A.; Johnston, S.; Shannon, R.; Voronkov, M.; Ward, C.; Banyer, J.; Hancock, P.; Murphy, T.; et al. (Oxford University Press, 2016)
We use observations from the Boolardy Engineering Test Array (BETA) of the Australian Square Kilometre Array Pathfinder (ASKAP) telescope to search for transient radio sources in the field around the intermittent pulsar PSR J1107-5907. The pulsar is thought to switch between an "off" state in which no emission is detectable, a weak state and a strong state. We ran three independent transient detection pipelines on two-minute snapshot images from a 13 hour BETA observation in order to 1) study the emission from the pulsar, 2) search for other transient emission from elsewhere in the image and 3) to compare the results from the different transient detection pipelines. The pulsar was easily detected as a transient source and, over the course of the observations, it switched into the strong state three times giving a typical timescale between the strong emission states of 3.7 hours. After the first switch it remained in the strong state for almost 40 minutes. The other strong states lasted less than 4 minutes. The second state change was confirmed using observations with the Parkes radio telescope. No other transient events were found and we place constraints on the surface density of such events on these timescales. The high sensitivity Parkes observations enabled us to detect individual bright pulses during the weak state and to study the strong state over a wide observing band. We conclude by showing that future transient surveys with ASKAP will have the potential to probe the intermittent pulsar population.